Profitability Ratio Analysis Of Capital Structure At Pt. Sekar Bumi, Tbk. - Setiani, Richa Anugrah (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
In the current era of globalization, advances in science and technology have caused world economic activities to develop very rapidly. The company's goal is to maximize profits. To measure the level of profit used profitability ratios. The profitability of a company can be influenced by the inventory used for the continuity of a production process. The purpose of this study was to determine whether there is an effect of the ratio of Net Profit Margin (NPM), Gross Profit Margin (GPM), Return On Assets (ROA), and Return On Equity (ROE) on the Debt to Equity Ratio (DER) at PT. Sekar Earth. Tbk. Population for 15 Years. Sampling using purposive sampling method so that the number of samples obtained is 10 years. The data analysis technique used is carried out with the help of the Statistical Package For The Social Science (SPSS) program, namely by performing multiple linear regression analysis which is carried out to determine the dependence of a dependent variable with two or more independent variables through a test requirement, namely passing the classical assumption test consisting of from normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. and tested the hypothesis. The results of this study indicate that the Net Profit Margin (NPM) has a positive and insignificant effect on the Debt to Equity Ratio (DER) at PT. Sekar Bumi, Tbk. Gross Profit Margin (GPM) has a negative and insignificant effect on the Debt to Equity Ratio (DER) at PT. Sekar Bumi, Tbk. Return on Assets (ROA) has a negative and significant effect on the Debt to Equity Ratio (DER) at PT. Sekar Bumi, Tbk. And Return On Equity (ROE) has a positive and significant effect on the Debt to Equity Ratio (DER) at PT. Sekar Bumi, Tbk.